Efektivitas Rehabilitasi Korban Penyalahgunaan Napza di Yayasan Rumoh Geutanyoe Aceh - Indri aprilia Maryufli ibrahim (JAROW: Journal of Ar-Raniry on Social Work, 2023)
Indonesia is one of the countries that will be a drug emergency in law number 35 of 2009 concerning drugs which states that "drug addicts and victims of drug abuse must undergo medical rehabilitation and social rehabilitation. The purpose of this study is to describe how the implementation of rehabilitation of victims of drug abuse and how the effectiveness of the rehabilitation program, especially at Yayasan Rumoh Geutanyoe Aceh. The research method used is a qualitative research method with a descriptive approach. Data collection using observation, interviews and documentation with 7 informants, namely 1 foundation administrator, 3 staff and 3 clients. The results of this study indicate that the form of rehabilitation implementation used is a form of non-medical rehabilitation (social) inpatient with a duration of 6 (six) months, as well as outpatient with a duration of 3 (three) months. The impact obtained from the social rehabilitation program is that clients become more diligent and enthusiastic, are able to mature themselves and choose better associations, can control emotions, and clients who have completed their rehabilitation period and function socially.